How Firm Characteristics Affect the Timeliness of Financial Disclosures in Nigerian Insurance Firms - Olubukola Sarah, Oyewole; C.S.A. Okeke , Frankline; Okeke, Oluchukwu Gloria; Nugroho, Moh Agus; Beactrice Chinonye , Ezeilo (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
Increasing the relevance of corporate financial statements to decision-making processes necessitates rapid availability of financial information to users. This study delves into the timely reporting practices of Nigerian insurance companies over a twelve-year period, spanning from 2009 to 2021. Through an examination of firm characteristics such as size and age, alongside the timeliness of financial reports measured by audit report delay, this research sheds light on the intricate dynamics influencing financial reporting practices within the Nigerian insurance sector. Utilizing advanced statistical analysis techniques including fixed effect modeling and diagnostic tests for data normality and heteroskedasticity, the findings unearth compelling insights. Notably, while firm size exhibits a significant negative impact on financial reporting timeliness, the influence of firm age proves to be less straightforward, indicating nuanced factors at play. This study underscores the imperative for insurance companies to bolster their asset bases, thereby enhancing their capacity to mitigate delays in financial reporting. By elucidating the interplay between firm characteristics and reporting timeliness, this research offers actionable recommendations to fortify the integrity and efficiency of financial reporting practices within the Nigerian insurance industry.